The Effect of Administration of Red Guava Juice (Psidium guajava) on The Hemoglobin Levels of Breast Cancer Patients Undergoing Chemotherapy - Sofya Husrianti; Suhaema Suhaema; Retno Wahyuningsih; Joyeti Darni (Poltekkes Kemenkes Mataram, 2026)
Background: Breast cancer patients undergoing chemotherapy may experience side effects such as anaemia due to the use of chemotherapy drugs. Anaemia in cancer patients can worsen clinical conditions and reduce quality of life. One non-pharmacological approach that may help increase haemoglobin levels is the consumption of red guava, which contains beneficial nutrients such as vitamin C, iron, and lycopene, which play a role in increasing haemoglobin levels. Research Methods: This study is a quantitative study using a pre-experimental design with a one-group pretest-posttest design. The study involved 15 participants with breast cancer-related anaemia who were undergoing chemotherapy. The intervention consisted of 250 ml of red guava juice, made from 200 g of guava and 50 ml of water, taken in the morning for 7 days. Measurements were taken using a haemoglobinometer or blood chemistry analysis. Research Results: The administration of red guava juice resulted in a significant change in the subjects’ haemoglobin levels; the mean haemoglobin level before the intervention was 10.4 g/dL ± 1.12 and increased to 11.7 g/dL ± 1.34 (p = 0.001). Conclusion: The administration of red guava juice (Psidium guajava) significantly increased haemoglobin levels in breast cancer patients undergoing chemotherapy.